LICENSURE EXAMINATION: STUDENTS’ INTRINSIC AND EXTRINSIC FACTORS AS SUCCESS PREDICTOR - Melvi A Briones,LPT (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
Preparation to pass the licensure examination is vital at the very first stage of college life. This study aimed to determine the freshmen students’ intrinsic and extrinsic factors as success predictors for their licensure examination. The descriptive- correlation method was employed to determine the intrinsic and extrinsic motivation and the significant differences between the respondents’ motivation among colleges and between the factors. One hundred ninety-four (194) students were utilized as respondents of this study. FGD with five (5) deans from different colleges were employed for validation and intervention. Results revealed that between the factors, intrinsic is the highest motivating factor. Respondents believe that to pass the board exam, their effort to develop their own skills will bring them success. They also believe that providing material things and other support for their family as an external motivation will just follow. The test on significant difference revealed that students’ perception of motivation from among colleges have no significant difference. However, between the factors, a significant difference was noted. Activities on study habits and skills formation of students will boost intrinsic motivation and family-centered activities were seen as an effective intervention program.